2016
DOI: 10.1101/088526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy Mitigates High-Temperature Injury in Pollen Development of Arabidopsis thaliana

Abstract: Highlights In Arabidopsis, autophagy is not essential for completion of the life cycle under normal temperatures. High temperature (HT) stress induces autophagy in developing anther wall cells and microspores. Autophagy deficient atg mutants become almost completely male-sterile at moderate HT. Autophagy plays a role in tapetum degeneration and pollen development during HTcaused abortion of tapetal program cell death. AbstractAutophagy is one of the cellular processes that break down cellular components du… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(84 reference statements)
0
3
0
1
Order By: Relevance
“…Autophagy mutant lines demonstrated both decreased flux to net protein synthesis and increased respiration compared to non‐mutants, thereby highlighting the importance of autophagy during carbon starvation for supplying energy (Avin‐Wittenberg et al, 2015). A more recent study focusing again on A. thaliana observed that autophagy deficient mutants demonstrated almost complete male sterility under high temperatures where wild‐type lines did not (Dündar et al, 2019), thus demonstrating the importance of autophagy to address the increasing respiratory demand of reproductive structures and microspores during heat stress. It is further interesting to note that in our querying of the response of genes involved in photosynthetic regulation (Wang et al, 2017) to heat stress in A. thaliana pollen, BRASSINAZOLE‐RESISTANT1 ( BZR1 ) is significantly up‐regulated in response to heat stress (Figure 2c).…”
Section: Net Carbon Gain As a Limiting Factor For Reproductive Development And Output During Heat Stressmentioning
confidence: 99%
“…Autophagy mutant lines demonstrated both decreased flux to net protein synthesis and increased respiration compared to non‐mutants, thereby highlighting the importance of autophagy during carbon starvation for supplying energy (Avin‐Wittenberg et al, 2015). A more recent study focusing again on A. thaliana observed that autophagy deficient mutants demonstrated almost complete male sterility under high temperatures where wild‐type lines did not (Dündar et al, 2019), thus demonstrating the importance of autophagy to address the increasing respiratory demand of reproductive structures and microspores during heat stress. It is further interesting to note that in our querying of the response of genes involved in photosynthetic regulation (Wang et al, 2017) to heat stress in A. thaliana pollen, BRASSINAZOLE‐RESISTANT1 ( BZR1 ) is significantly up‐regulated in response to heat stress (Figure 2c).…”
Section: Net Carbon Gain As a Limiting Factor For Reproductive Development And Output During Heat Stressmentioning
confidence: 99%
“…ATG18d、VPS34 的表达量也上调 [72] 。ATGs 基因功能缺失或下调都会损害植株对 营养胁迫的抗性。例如,玉米 atg12 突变体在氮缺乏时表现出叶片衰老提前、产 量下降, 氮转运能力下降, 氮收获指数 (种子氮含量与整株氮含量比值) 下降 [73] 。 相反地,苹果过表达 ATG18a 后低氮下叶片的硝酸盐含量增加,并提高对低氮胁 迫的耐受性 [74] 。在营养缺乏时,植物还可以通过自噬将叶绿体中的氮调动到其 他所需的器官,如拟南芥光合碳固定酶 Rubisco 作为叶绿体高丰度蛋白,可以被 转移到液泡中,在饥饿条件下通过 ATG 依赖的自噬降解 [114] 。此外,也有研究表 明过量氮供应诱导的叶绿体自噬可以抑制拟南芥的磷饥饿, 表明自噬作为营养调 控的中枢可以综合协调磷饥饿下氮、碳的有效性,从而提高缺磷抗性 [115] 。 大量研究表明, 不适温度等非生物胁迫可以诱导植物自噬来提高植物的抗性。 低温和高温胁迫显著诱导了 ATGs 的表达和自噬小泡的形成 [42,79,116,117] 。不适温 度下,植物细胞中不可溶蛋白聚集、氧化蛋白会大量积累 [118] 。番茄 ATG5、ATG7 和选择自噬受体 NBR1 沉默植株对热胁迫敏感,表现为热胁迫后光合效率和光合 能力下降,叶片萎蔫严重,并积累更多的不溶性蛋白 [41,42] ;而苹果 ATG18a 过表 达植株提高了植株的耐热性,叶绿体损伤显著降低、光合增强,抗氧化酶活性增 强 [78] 。沉默 ATG2、ATG6 和 NBR1 也导致低温下番茄叶片中光保护的功能性蛋 白含量减少,泛素化蛋白积累增加,植株抗冷性下降 [79] 。自噬在植物热应激记 忆重置中也具有调节作用。 拟南芥 atg 突变体中被热激诱导的热休克蛋白 (HSPs,…”
Section: 自噬在非生物胁迫中的作用 自噬在植物应对营养饥饿时起着至关重要的作用, 营养饥饿通过诱导自噬小unclassified
“…Autophagy can be induced by various abiotic stresses, including heat, cold, drought, osmotic, and salt stress, to improve plant resistance ( Slavikova et al, 2008 ; Dündar et al, 2019 ; Sedaghatmehr et al, 2019 ; Bao et al, 2020 ; Chi et al, 2020 ; Jung et al, 2020 ; Thirumalaikumar et al, 2021 ). TOR kinase, which is crucial for autophagy induction, works downstream of SnRK1 ( Soto-Burgos and Bassham, 2017 ).…”
Section: Induction Of Autophagy By Abiotic Stress Signalsmentioning
confidence: 99%